2015 IEEE Eindhoven PowerTech 2015
DOI: 10.1109/ptc.2015.7232570
|View full text |Cite
|
Sign up to set email alerts
|

Control of DC bus voltage with a Modular Multilevel Converter

Abstract: is an open access repository that collects the work of Arts et Métiers ParisTech researchers and makes it freely available over the web where possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…In this section a control structure, equivalent to the control of the AAM described in [11], is presented for the simplified MMC model. As in the two-level VSC, a control strategy based on two cascaded loops (namely inner and outer loops) is proposed.…”
Section: E MMC Controlmentioning
confidence: 99%
See 2 more Smart Citations
“…In this section a control structure, equivalent to the control of the AAM described in [11], is presented for the simplified MMC model. As in the two-level VSC, a control strategy based on two cascaded loops (namely inner and outer loops) is proposed.…”
Section: E MMC Controlmentioning
confidence: 99%
“…The latter can be a constant value as considered in [3] (upper position of the switch in Fig. 5) or it can be associated with the square of the DC voltage v 2 dc as discussed in [11] (lower position of the same switch). The latter allows sharing the MMC stored energy with the DC bus.…”
Section: E MMC Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…In [19], it has been demonstrated that can be controlled by the dc component of the differential current and by the ac component of the differential current. All the different loops are represented in Fig.…”
Section: Energy-based Model Of the MMCmentioning
confidence: 99%
“…Equation (19) shows that the equivalent capacitor for the regulation of the DC bus now integrates the capacitors of MMC, which induces a high increase for the capacitor value. For example, in this case study the value of the MMC capacitors (6C tot ) is 24 times the value of a 70-km DC cable capacitor.…”
Section: ) Two Different Ways For the DC Voltage Controlmentioning
confidence: 99%